Pendekatan Storytelling: Penanaman Akhlak Mulia Menghormati Orang Tua dan Guru Pada Anak-Anak TPQ Al-Haji Palangka Raya - Redha Anshri, muhammad; faujianor, fauji; ahmat fauzi, nurul; surawan, surawan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This community service activity aims to instill noble moral values, particularly respect for parents and teachers, in the children of TPQ Al-Haji Palangka Raya through storytelling. The method used is Service Learning, which combines community service with reflective learning. The activity is carried out in three stages: preparation, implementation, and reflection. During the preparation stage, researchers conducted observations and interviews with TPQ administrators to understand the children's needs, then designed storytelling materials containing moral values. The implementation stage involved interactive storytelling sessions, discussions, and role-playing to practice respect for parents and teachers. Data was collected through participatory observation, semi-structured interviews, and documentation. The reflection stage was conducted to evaluate the impact of the activity and the learning gained by the service team. The results showed an increase in the children's understanding of the importance of respecting parents and teachers, as well as their enthusiasm in participating in the activities. The service team also gained valuable experience in managing educational activities and understanding the social context of the community. This activity proves that storytelling is effective in instilling moral values in children. It is hoped that this approach can be widely adopted in moral education at TPQ and other educational institutions, contributing to the formation of a generation with strong character and noble ethics.